2014
DOI: 10.1371/journal.pone.0113122
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Association of Hazardous Alcohol Use with Hypertension in an Urban Cohort of People Living with HIV in South Florida

Abstract: ObjectiveIndustrialized countries are currently experiencing an epidemic of high blood pressure (HBP) extending to people living with HIV (PLWH). Given the prevalence of hazardous alcohol use (HAU), this study examines the relationship between alcohol consumption and hypertension in PLWH. Including a gender analysis is critical, given the high rates of HAU and HIV among females.MethodWe followed PLWH including both HAU and non-HAU (200 each). Participants were assessed twice for body weight, blood pressure, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Besides, our study also identified a more significant impact of tobacco use on females, consistent with the findings of previous studies in China [10]. Though consistent with the finding of Hui et al (2018) [10] that there was more impact of alcohol consumption on females, other researchers identified a more significant association between alcohol intake and hypertension risk for males [9,11,49]. This inconsistency may be due to the fact that only the status of ever drinking was considered in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides, our study also identified a more significant impact of tobacco use on females, consistent with the findings of previous studies in China [10]. Though consistent with the finding of Hui et al (2018) [10] that there was more impact of alcohol consumption on females, other researchers identified a more significant association between alcohol intake and hypertension risk for males [9,11,49]. This inconsistency may be due to the fact that only the status of ever drinking was considered in our study.…”
Section: Discussionsupporting
confidence: 92%
“…This inconsistency may be due to the fact that only the status of ever drinking was considered in our study. However, the type-of alcohol, frequency, and the amount of alcohol intake may also matter [9,49].…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, chronic excessive alcohol consumption causes cardiometabolic disorders, 24 and hazardous alcohol use may increase the risk of hypertension in PLWH. 25 Despite the fact that the life expectancy of PLWH on antiretroviral therapy (ART) has approached that of the general population, the habit of smoking or excessive alcohol intake within this group might curtail their life expectancy and elevate overall mortality risks. 26 Therefore, educating PLWH regarding smoking/ alcohol cessation is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto al consumo de alcohol, se muestra que en los hombres éste puede ser mayor que en las mujeres 19 la administración aguda de nicotina a humanos o animales, aparentemente, tienen un efecto en las mediciones de norepinefrina (o noradrenalina), proponiéndose la hipótesis de que esta droga produce efectos psicológicos por la alteración del sistema de señalización noradrenérgico. Esta forma de administración de la nicotina produce una estimulación muy potente al sistema nervioso central en humanos, produciendo un incremento en el promedio de la presión arterial, ritmo cardiaco, y niveles plasmáticos de norepinefrina, pero el tabaquismo crónico no se asocia con presión arterial elevada 17,20,21 , aunque en mujeres, en un estudio en Nepal, se observó que el fumar activamente es factor de riesgo para el aumento de la presión arterial 22 .…”
Section: Discussionunclassified